2015
DOI: 10.1111/bph.13187
|View full text |Cite
|
Sign up to set email alerts
|

What can isolated skeletal muscle experiments tell us about the effects of caffeine on exercise performance?

Abstract: Caffeine is an increasingly popular nutritional supplement due to the legal, significant improvements in sporting performance that it has been documented to elicit, with minimal side effects. Therefore, the effects of caffeine on human performance continue to be a popular area of research as we strive to improve our understanding of this drug and make more precise recommendations for its use in sport. Although variations in exercise intensity seems to affect its ergogenic benefits, it is largely thought that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
85
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 75 publications
(99 citation statements)
references
References 72 publications
(164 reference statements)
4
85
0
5
Order By: Relevance
“…Second, caffeine and vehicle did not significantly differ in their effects on interscapular brown fat temperature. The effect of caffeine on muscle work efficiency and thermogenesis seen here is consistent with the known ability of caffeine to enhance muscle power and exercise endurance . and reduce perceived exertion .…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Second, caffeine and vehicle did not significantly differ in their effects on interscapular brown fat temperature. The effect of caffeine on muscle work efficiency and thermogenesis seen here is consistent with the known ability of caffeine to enhance muscle power and exercise endurance . and reduce perceived exertion .…”
Section: Discussionsupporting
confidence: 86%
“…Caffeine affects not only energy balance but also exercise endurance and performance . Caffeine can increase muscle performance, energy expenditure (EE), thermogenesis, and fuel utilization through several potential mechanisms .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, recent research has demonstrated that ergogenic benefit with NaHCO3 ingestion is most likely observed for TLIM at 100% WPEAK (Higgins et al 2013a). Similarly, Simmonds et al (2010) demonstrated that 5 mg.kg -1 caffeine increased TLIM at 120% V O2PEAK by ~15% although the ergogenic effects of caffeine are generally more pronounced in trained compared to non-trained individuals (Simmonds et al 2010;Tallis et al 2015).…”
Section: Introductionmentioning
confidence: 97%
“…For example, although each study adopted a dosage of 5 0.3 g.kg -1 NaHCO3, the dosage of caffeine varied between studies with Pruscino et al (2008) and Carr et al (2011) adopting ~6 mg.kg -1 whereas Kilding et al (2012) and Christensen et al (2014) adopted 3 mg.kg -1 . Additionally there were differences in approaches to abstinence of caffeine intake prior to exercise, an area recognised to limit the ability to compare studies evaluating the ergogenic effects of caffeine (Tallis et al 2015). For example, participants in Carr et al (2011) and Pruscino et al (2008) abstained for 48 hours prior to exercise whereas participants in Kilding et al (2012) abstained for the duration of the study.…”
Section: Introductionmentioning
confidence: 99%